Beyond yellow English : toward a linguistic anthropology of Asian Pacific America - Reyes, Angela, 1970-; Lo, Adrienne (New York ; Oxford : Oxford University Press, 2009)
This volume examines issues of language, identity, and culture among the rapidly growing Asian Pacific American (APA) population. It cover topics such as media representations of APAs, codeswitching and language crossing, and narratives of ethnic identity.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sociolinguistics -- United States; Asian Americans -- Languages; Asian Americans -- Ethnic identity; Asian Americans and mass media; Language and education -- United States